Peran Koperasi Syariah BMT BUMI dalam Meningkatkan Kualitas Usaha Mikro - Lindiawatie, Lindiawatie; Shahreza, Dhona (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2018)
This research aims to analyze the role of active Islamic cooperative in improving the quality of the micro enterprise and know the kinds of cooperative role of Sharia in improving quality of micro enterprises.Qualitative research methods are methods with data retrieval through structured interviews, field observations and documentation.The results of the research show that the BMT BUMi has run its role in General as a cooperative of Sharia that are able to make economic and social activities of its members which is the community around the mosque became a better and prosperous, while the types of initiatives that have been undertaken by the BMT BUMi in the improved quality of micro enterprises only on the physical aspects of the marketing of products and haven't touched aspects of marketing management services (quality of service), production management, financial management, simple accounting, human resource management and business ethics.